Yield management jako metoda zarządzania operacyjnego w przedsiębiorstwie turystycznym - Gryszel, Piotr (Yield Management as the Method of Operational Management in a Tourist Enterprise, 2008)
Tourist market is to a great extend characterized by the concentration of demand in time and space, i.e. significant seasonality during a year, month, week or even a day and night period. Seasonal intensity of demand does not always have positive influence on making use of the services capacity represented by a particular tourist enterprise. Yield management, presented in the hereby article, is the method of operational management, which may alleviate the results of seasonal tourist demand. It facilitates such management of service prices which encourages clients to take advantage of the services provided by an enterprise in the period of low season. On the other hand, in the periods of peak season it allows for maximizing income and profits resulting from an enterprises business activity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 166-181